Synthesis and properties of tetrathiafulvalenes bearing 6-aryl-1,4-dithiafulvenes - Yoshimura, Aya; Kimura, Hitoshi; Kagawa, Kohei; Yoshioka, Mayuka; Itou, Toshiki; Vasu, Dhananjayan; Shirahata, Takashi; Yorimitsu, Hideki; Misaki, Yohji (Beilstein Journal of Organic Chemistry, 2020)
Novel multistage redox tetrathiafulvalenes (TTFs) bearing 6-aryl-1,4-dithiafulvene moieties were synthesized by palladium-catalyzed direct C–H arylation. In the presence of a catalytic amount of Pd(OAc)2, P(t-Bu3)·HBF4, and an excess of Cs2CO3, the C–H arylation of TTF with several aryl bromides bearing 1,3-dithiol-2-ylidenes took place efficiently to produce the corresponding π-conjugated molecules. We also succeeded in the estimation of the oxidation potentials and number of electrons involved in each oxidation step of the obtained compounds by digital simulations.
Keywords: cross-conjugated systems; electrochemical properties; extended π-conjugation; digital simulation analysis; tetrathiafulvalene

TTF Chemistry-Fundamental and Applications of Tetrathiafulvalene - Yamada, J.; Sugimoto, T. (Kodansha-Springer, 2004)

(untitled) - Canevet, D.; Sallé, M.; Zhang, G.; Zhang, D.; Zhu, D. (Chem. Commun., 2009)

(untitled) - Gorgues, A.; Hudhomme, P.; Sallé, M. (Chem. Rev., 2004)

(untitled) - Segura, J. L.; Martín, N. (Angew. Chem., Int. Ed., 2001)

(untitled) - Iyoda, M.; Hasegawa, M.; Miyake, Y. (Chem. Rev., 2004)

Organic Redox Systems - Hasegawa, M.; Iyoda, M. (Tetrathiafulvalene: A Redox Unit for Functional Materials and a Building Block for Supramolecular Self-Assembly, 2015)

(untitled) - Misaki, Y. (Sci. Technol. Adv. Mater., 2009)

ECS Meeting Abstracts, Volume MA2008-01, B1- Batteries General Session, Abstract #167 - Inatomi, Y.; Hojo, N.; Yamamoto, T.; Shimada, M.; Watanabe, S. (Examination of Multi-Electron Reaction Type pi-Conjugated Organic Compounds as Cathode Active Material for Rechargeable Power Supply, 213th ECS meeting, Phoenix, Arizona, 18.5.2008-22.5.2008, 2008)

(untitled) - Inatomi, Y.; Hojo, N.; Yamamoto, T.; Watanabe, S.-i.; Misaki, Y. (ChemPlusChem, 2012)

(untitled) - Kato, M.; Ogi, D.; Yao, M.; Misaki, Y. (Chem. Lett., 2013)

(untitled) - Kato, M.; Senoo, K.-i.; Yao, M.; Misaki, Y. (J. Mater. Chem. A, 2014)

(untitled) - Iwamoto, S.; Inatomi, Y.; Ogi, D.; Shibayama, S.; Murakami, Y.; Kato, M.; Takahashi, K.; Tanaka, K.; Hojo, N.; Misaki, Y. (Beilstein J. Org. Chem., 2015)

(untitled) - Yamauchi, T.; Shibata, Y.; Aki, T.; Yoshimura, A.; Yao, M.; Misaki, Y. (Chem. Lett., 2018)

(untitled) - Ogi, D.; Fujita, Y.; Kato, M.; Yamauchi, T.; Shirahata, T.; Yao, M.; Misaki, Y. (Eur. J. Org. Chem., 2019)

(untitled) - Yamauchi, T.; Kato, M.; Shirahata, T.; Yao, M.; Misaki, Y. (Chem. Lett., 2019)

(untitled) - Bryce, M. R. (J. Mater. Chem., 2000)

(untitled) - Coffen, D. L.; Chambers, J. Q.; Williams, D. R.; Garrett, P. E.; Canfield, N. D. (J. Am. Chem. Soc., 1971)

(untitled) - Ueno, Y.; Okawara, M. (Chem. Lett., 1974)

(untitled) - Ueno, Y.; Nakayama, A.; Okawara, M. (J. Am. Chem. Soc., 1976)

(untitled) - Yoneda, S.; Kawase, T.; Inaba, M.; Yoshida, Z.-i. (J. Org. Chem., 1978)

(untitled) - Le Coustumer, G.; Mollier, Y. (J. Chem. Soc., Chem. Commun., 1980)

(untitled) - Babeau, A.; Tinh, N. H.; Gasparoux, H.; Polycarpe, C.; Torreilles, E.; Giral, L. (Mol. Cryst. Liq. Cryst., 1982)

(untitled) - Starodub, V. A.; Baumer, V. N.; Guella, I. M.; Golovkina, I. F.; Alyoshin, V. G.; Nemoshkalenko, V. V.; Senkiewicz, A. I. (Synth. Met., 1983)

(untitled) - Tsujimoto, K.; Okeda, Y.; Ohashi, M. (J. Chem. Soc., Chem. Commun., 1985)

(untitled) - Charlton, A.; Underhill, A. E.; Williams, G.; Kalaji, M.; Murphy, P. J.; Hibbs, D. E.; Hursthouse, M. B.; Malik, K. M. A. (Chem. Commun., 1996)

(untitled) - Charlton, A.; Underhill, A. E.; Williams, G.; Kalaji, M.; Murphy, P. J.; Malik, K. M. A.; Hursthouse, M. B. (J. Org. Chem., 1997)

(untitled) - Gompper, R.; Hock, J. (Synth. Met., 1997)

(untitled) - Zotti, G.; Zecchin, S.; Schiavon, G.; Berlin, A.; Huchet, L.; Roncali, J. (J. Electroanal. Chem., 2001)

(untitled) - Kakinuma, T.; Kojima, H.; Kawamoto, T.; Mori, T. (J. Mater. Chem. C, 2013)

(untitled) - Mitamura, Y.; Yorimitsu, H.; Oshima, K.; Osuka, A. (Chem. Sci., 2011)

(untitled) - Gholami, M.; Tykwinski, R. R. (Chem. Rev., 2006)

(untitled) - Sugimoto, T.; Awaji, H.; Misaki, Y.; Yoshida, Z.-i.; Kai, Y.; Nakagawa, H.; Kasai, N. (J. Am. Chem. Soc., 1985)

(untitled) - Sugimoto, T.; Misaki, Y.; Arai, Y.; Yamamoto, Y.; Yoshida, Z.-i.; Kai, Y.; Kasai, N. (J. Am. Chem. Soc., 1988)

(untitled) - Misaki, Y.; Matsumura, Y.; Sugimoto, T.; Yoshida, Z.-i. (Tetrahedron Lett., 1989)

(untitled) - Amaresh, R. R.; Liu, D.; Konovalova, T.; Lakshmikantham, M. V.; Cava, M. P.; Kispert, L. D. (J. Org. Chem., 2001)

(untitled) - Rajagopal, D.; Lakshmikantham, M. V.; Cava, M. P. (Org. Lett., 2002)

(untitled) - Coffin, M. A.; Bryce, M. R.; Batsanov, A. S.; Howard, J. A. K. (J. Chem. Soc., Chem. Commun., 1993)

(untitled) - Bryce, M. R.; Coffin, M. A.; Skabara, P. J.; Moore, A. J.; Batsanov, A. S.; Howard, J. A. K. (Chem. – Eur. J., 2000)

(untitled) - Hasegawa, M.; Fujioka, A.; Kubo, T.; Honda, T.; Miyamoto, H.; Misaki, Y. (Chem. Lett., 2008)

(untitled) - Horiuchi, H.; Misaki, Y. (Chem. Lett., 2010)

(untitled) - Nishiwaki, M.; Tezuka, M.; Shirahata, T.; Misaki, Y. (Chem. Lett., 2011)

Gaussian 16, Revision C.01 (Gaussian, Inc., 2019)

DigiElch 7 Prof software (Elchsoft)